The lncRNA, Nespas, Is Associated with Osteoarthritis Progression and Serves as a Potential New Prognostic Biomarker - Park, Sujung (Cartilage, 2017)
Introduction. In this article, we explored the hypothesis that the long noncoding RNA, Nespas, promotes osteoarthritis (OA) by supporting abnormal lipid metabolism in human chondrocytes. Materials and Methods. Human articular chondrocytes from osteoarthritis patients were used and expression level of Nespas were determined by real-time polymerase chain reaction. Introduction of Nespas and Nespas-associated genes/miRNAs were performed by using a lentiviral system. The effect of Nespas on mitochondrial function was determined by staining mitochondria and analyzing mitopotential and mitochondrial genes. Moreover, to identify the responsible molecules in Nespas-induced pathogenesis, profiling of peroxisomal genes and miRNAs were applied and interactome analysis was performed. Results. Highly elevated levels of Nespas and Acyl-CoA synthetase 6 (ACSL6) were observed in OA patients. Both Nespas overexpression and ACSL6 upregulation into human chondrocytes induced typical OA characteristics, such as downregulation of type II collagen; upregulation of type I collagen, metalloproteinase 13, and caspase-1 and -3; and dysfunction of mitochondria and peroxisome. Co-expression of Nespas and ACSL6 siRNA reduced caspase-1 and -3 levels. Moreover, Nespas overexpression significantly suppressed levels of miR-291a-3p, -196a-5p, -23a-3p, -24-3p, and let-7a-5p, and these miRs are known to potentially target ACSL6 according to ingenuity pathway analysis. We also confirmed that these miRs were significantly suppressed in human OA chondrocytes. Overexpression of miR-291a-3p, -196a-5p, -23a-3p, -24-3p, or let-7a-5p in the presence of Nespas suppressed levels of ACSL6, caspase-1 and -3. Discussion. Overall, we suggest that elevated Nespas level in OA are associated with OA pathogenesis by suppressing miRs targeting ACSL6 and subsequent ACSL6 upregulation.